Como as enfermeiras enfrentam o emergir do estresse no seu trabalho - Oliveira, Jacira dos Santos (1999)
Stress is complex and it requires responses equally complexes. It can be caused to person by internai or externai stressor agents. This research lias an exploratory and descriptive natures and its goals was: to aprehend some factors that put the nurses in alarni State, identify the organic and psychological reactions experienced by lhe nurses when they faced some stress situations, and investigate the coping fornis adopted by the nurses in a stress encounter situation. The research was carried out in a public school-hospital in Fortaleza, Ceará, ind the subjects were 07 (seven) nurses involved in 16 (sixteen) stress situations, and the research was Iheoretically based on Lazarifs coping stress theory. With this research was obtained the residis below: the predominant unchaining factors of the stress situations was the lack of support and the lack of specialized professionals in nursering, denianding the overburdening, and the activities control failure, the lack of material, equipnients and medicines, lhe nurses refered to feel ahnost all the biological reactions indicatede by Selye (1956) as characterizator of alann phase: anxiety, tension, worry, nervousness, tachycardia, sudoresis, hot wave, expectation, fear, headache, dental arch tension, offense feeling, anger. The stress situations ranked as challenge obtained larger punctuation nuniber on the assessnient made by the research subjects. The coping forin focused on the problem was adopted by the nurses majority involved on the research. Thus, it is the most secure, with the possibilities of the satisfactory results. Besides. it gives the person the opportunity to experience and matureness of the adaptative resourses. The author intends to conimunicate the results of the research to the nurses of the institution, to form an interest group and together to seek collective way forms of coping, as well as to support the existence groups. Thus, the author intends to contribute to the adequate work quality improving of the nurses.